Energy Recovery signs VorTeq licencing deal with Schlumberger. Issue 10 (October 2015) - Unknown
Abstract : Energy Recovery Inc has entered into a 15-year agreement with oilfield services company Schlumberger Technology Corp providing exclusive rights to its VorTeq hydraulic pumping system.